‘It’s such a blackbox function’: Norwegian academic librarians’ ambivalent perceptions towards AI use in academic libraries and academia - Bøyum, Idunn; Khosrowjerdi, Mahmood (Information research, 2025)
Introduction. In this study we report on the perceptions of Norwegian academic librarians towards the emergent role of AI in academic libraries, both in service delivery and library operations. Method. A qualitative study was conducted through semi-structured interviews with eight academic librarians at two Norwegian universities. Analysis. The interview transcriptions were inductively analysed and coded using F4analyse. Results. Most participants had positive experiences with AI in various tasks and acknowledged its influence on teaching information literacy. However, they expressed scepticism towards AI due to transparency and data security concerns. The lack of guidelines led to uncertainty in their roles, and practices varied across universities regarding AI applications for students. Conclusion: The study reveals academic librarians’ perceptions of AI as a double-edged sword, offering benefits but also presenting challenges, particularly related to ethical issues. Frustration was expressed over the lack of unified AI implementation guidelines, causing uncertainty among librarians and students. These underscore the need for clear AI guidelines and enhancement of librarians’ AI competence.